Electrical properties and microstructural characterization of Ni/Ta contacts to n-type 6H–SiC - 周天宇 刘学超 黄维 卓世异 郑燕青 施尔畏 (Chinese physics B, 2015)
A Ni/Ta bilayer is deposited on n-type 6H–SiC and then annealed at different temperatures to form an ohmic contact. The electrical properties are characterized by I–V curve measurement and the specific contact resistance is extracted by the transmission line method. The phase formation and microstructure of the Ni/Ta bilayer are studied after thermal annealing. The crystalline and microstructure properties are analyzed by using glance incident x-ray diffraction（GIXRD）,Raman spectroscopy, and transmission electron microscopy. It is found that the transformation from the Schottky to the Ohmic occurs at 1050℃ and the GIXRD results show a distinct phase change from Ta2C to TaC at this temperature. A specific contact resistance of 6.5×10^-5Ω·cm^2is obtained for sample Ni（80 nm）/Ta（20 nm）/6H–SiC after being annealed at 1050℃. The formation of the TaC phase is regarded as the main reason for the excellent Ohmic properties of the Ni/Ta contacts to 6H–Si C. Raman and TEM data reveal that the graphite carbon is drastically consumed by the Ta element, which can improve the contact thermal stability. A schematic diagram is proposed to illustrate the microstructural changes of Ni/Ta/6H–SiC when annealed at different temperatures.